Um/a amigo/a para Mafalda : tirinhas, leitura e produção textual - Vieira, Simária Santana Sales (2021)
This thesis, entitled “A friend for Mafalda: comic strips, reading and textual production”, aims to encourage students in the 8th grade class A, from a school of Education Office of Sergipe, to obtain reading and production skills of the comic strip genre. The focus of this intervention is concentrated on reading and producing comic strips, a genre with multiple uses of language and which are fundamental for the construction of meanings. The aim is to explore Mafalda's comic strips for presenting an interesting and diversified speech that fits perfectly in the current society, addressing social issues, criticisms and questions, in addition to irony. Mafalda's strips will also be the starting point of the students' final productions, “building a friend for Mafalda”, adding to this study because they deal with themes that are part of the sociocultural interaction in which the students are inserted. For this matter, it is essential a study in the light of theories from the perspective of reading, production and comic strip. For this reason, the research is carried out in the area of reader development, with a qualitative approach, based on studies by Brandão (1994), Marcuschi (2008), Vergueiro (2018), Bakhtin (2016), among other authors. From the perspective of classroom practice, the work is also composed of the workbook containing the didactic sequence used in the selected class. In order to carry out the activities, aglobalized reading is essential, in which the linguistic is conceived in parallel with the visual, which together form the basis of the comic strip genre. The final product of this study is a workbook containing the steps for the development of the didactic sequence, as well as the results obtained from it. The didactic sequence proposed here constitutes a reinforcement tool for the development of teaching work.